Subjective variables of Financial Well-being and Individual Economic Behavior: Pre-and Post- Financial Literacy Intervention - Chauhan, Rajni Rajan; Dhami, Dr. Jasdeep Kaur (The journal of contemporary issues in business and government, 2021)
Financial wellbeing is usually objectively measured and also views as a subjective concept that refers to "How people feel or evaluate themselves related to money matters". Personal economic well-being is a multifaceted subjective concept that includes subjective variables of Financial Well-being like financial satisfaction, financial behaviour, attitude, and perceptions of Individual related to financial decisions. In this multi-disciplinary experimental research, the paper focused on two objectives: 1) to study the relationship between subjective variables of Financial- wellbeing and 2) on observing variation in the subjective variables of Financial- wellbeing in both situations of Pre-and Post-Financial Literacy intervention. The sample of the study consists of 308 working people as respondents in tri-city Chandigarh. The questionnaire covers subjective variables of Financial-wellbeing, i.e., 1) Individual Economic Behaviour, 2) Financial-Awareness, 3) Financial- Perception, 4) Financial-Attitude, and 5) Socio-economic-demographic characteristics of respondents. The study reveals that: 1) a significant relationship between other subjective variables of Financial-wellbeing and Individual Economic Behavior among, 2) a significant relationship exists between Individual Economic Behaviour and socio-economic demographic variables, i.e., Income and employment level, 3) The paired t-test reveals that a substantial improvement in subjective variables of Financial-wellbeing and Individual Economic Behaviour in Post- Financial Literacy Intervention situation among working people in tri-city Chandigarh in Pre- and Post- Financial Literacy Intervention. Thus, Financial Literacy has a positive impact on Economic Behaviour and subjective variables of Financial-wellbeing among Individuals.